Contrasting the effect of risk- and non risk-based capital structure on insurers’ performance in Nigeria - Akpan, Sunday S.; Mahat, Fauziah; Amin Noordin, Bany Ariffin; Md Nassir, Annuar (MDPI, 2017)
Literature on capital-based regulation and performance of insurers in emerging market is not only limited; it is incomplete, particularly on a comparative basis. This has continuously attracts researchers’ interest and concerns for practitioners and policy makers. This paper therefore examines the effect of capital structure on performance of insurers comparatively before and after the implementation of risk-based capital (RBC) policy in Nigeria to determine which policy regime enables insurers to perform better. Descriptive statistics are employed to describe the characteristics of the data while the hypotheses are tested using two-stage estimation procedure of fixed and random effect models. Results reveal that insurance capital structure (measured by technical provision ratio) has a significant positive effect on insurance performance (measured by earnings per share and return on asset) during non-RBC regime when compared to RBC regime. Based on these findings, it is concluded that insurers in Nigeria performed better under non-RBC than RBC era. This finding provides important insight to managers, regulators and investors by fostering more understanding of how to manipulate and regulate insurance capital for performance optimization under RBC scenarios.